Response and Learning Outcomes of Digital Forest Predator Game (DFPG) Implementation in Elementary School - Fanani, Achmad; Kholidah, Nur Dyana; Azmy, Bahauddin; Wardani, Imas Srinana (Journal of Innovation in Educational and Cultural Research, 2025)
This study investigates the effectiveness of the "Digital Forest Predator Game" (DFPG), a digital escape room game designed to teach food web concepts to elementary students in Indonesia. Despite increasing integration of technology in education, elementary students continue to struggle with abstract ecological concepts, particularly in developing countries where both infrastructural and pedagogical barriers exist. Using a quantitative descriptive approach with a one-shot case study design, this research evaluated the implementation of DFPG among 27 fifth-grade students in Surabaya. Data collection employed student response questionnaires that measured three dimensions (interest/motivation, active involvement, and learning effectiveness), as well as concept comprehension tests. Results revealed positive student responses across all dimensions (Interest/Motivation: 3.2/4, Learning Effectiveness: 3.1/4, Active Involvement: 3.0/4) and strong learning outcomes with 70.4% of students achieving high scores (80-100 range) and a mean score of 84.36. The findings demonstrate that interactive digital games effectively bridge the gap between abstract ecological concepts and elementary students' understanding while simultaneously fostering digital literacy and problem-solving skills. This research contributes to educational science by providing empirical evidence of gamification's effectiveness in elementary ecology education and establishing a practical framework for integrating technology in resource-constrained educational settings.